Deciphering the causal association and co-disease mechanisms between psoriasis and breast cancer - Li, Xujia; Huang, Lingli; Yan, Yue; Rong, Yuming; Chen, Xuxian; Gao, Mengge; Huang, Jinsheng (Frontiers in Immunology, 2024)
Background: Prior research has indicated a link between psoriasis and the susceptibility to breast cancer (BC); however, a definitive causal relationship remains elusive. This study sought to elucidate the causal connection and shared underlying mechanisms between psoriasis and BC through bidirectional Mendelian randomization (MR) and bioinformatic approaches.We employed a bidirectional MR approach to examine the potential causal connection between psoriasis and BC. Genetic data pertaining to psoriasis and BC were sourced from extensive published genome-wide association studies. The inverse -variance weighted or wald ratio served as the primary method for estimating reciprocal causal effects. Sensitivity analysis of the MR results was applied with multiple methods. Leveraged datasets from the gene expression omnibusGene Expression Omnibus and the cancer genome atlasCancer Genome Atlas repositories to identify common differentially expressed genes, shedding light on the shared mechanisms underlying these two conditions.The MR analysis revealed that when considering Psoriasispsoriasis as an exposure factor, the incidenceincidences of BC was about 1.027 times higher (OR=1.027) and estrogen receptor negative (ER-) BC (OR=1.054) were higher than in the general population. When using theHer2+ BC subtype HER-2+ as an exposure factor, the risk of psoriasis was 0.822 times higher (OR=0.822) than in the general population. Sensitivity analysis indicated that the results were robust.Transcriptome analysis showed that CXCL13 and CCL20 were activated in both BC and psoriasis.Both diseases were also linked to neutrophil chemotaxis, the IL17IL-17 pathway, and the chemokine pathway.The results suggest that psoriasis may increase the risk of BC, especially ER-BC, while reverse MR suggests a decreased risk of psoriasis in HER-2Her2+ BC. Transcriptome analysis also revealed a shared mechanism between psoriasis and BC.